2014
DOI: 10.1098/rstb.2013.0140
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of PKMζ

Abstract: In contrast to protein kinases that participate in long-term potentiation (LTP) induction and memory consolidation, the autonomously active atypical protein kinase C isoform, protein kinase Mzeta (PKMζ), functions in the core molecular mechanism of LTP maintenance and long-term memory storage. Here, using multiple complementary techniques for light and electron microscopic immunolocalization, we present the first detailed characterization of the cellular and subcellular distribution of PKMζ in rat hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 53 publications
11
28
0
Order By: Relevance
“…To confirm that the apparent signal was representative of newly produced PKMζprotein, we used EELS to visualize Ce at the same synapse. We found that the Ce signal was enhanced at the postsynaptic membrane (Figure 5C and D at lower magnification, E and F at higher magnification) confirming that new copies of PKMζpreferentially localize to the post-synaptic membrane, consistent with previous reports for PKMζlocalization (Hernández, et al, 2014). Unstimulated neurons that were treated with BILN-2061 and analyzed similarly (Figure 5G–I) showed only a minimal signal for Ce by EELS in synapses (Figure 5J) despite comparable post-synaptic density staining in conventional EM.…”
Section: Resultssupporting
confidence: 91%
“…To confirm that the apparent signal was representative of newly produced PKMζprotein, we used EELS to visualize Ce at the same synapse. We found that the Ce signal was enhanced at the postsynaptic membrane (Figure 5C and D at lower magnification, E and F at higher magnification) confirming that new copies of PKMζpreferentially localize to the post-synaptic membrane, consistent with previous reports for PKMζlocalization (Hernández, et al, 2014). Unstimulated neurons that were treated with BILN-2061 and analyzed similarly (Figure 5G–I) showed only a minimal signal for Ce by EELS in synapses (Figure 5J) despite comparable post-synaptic density staining in conventional EM.…”
Section: Resultssupporting
confidence: 91%
“…Confocal microscopy revealed PKMζ in the sensorimotor cortex is compartmentalized in small puncta (Figure 3), similar to its distribution in the hippocampus (Hernández et al., 2014). The puncta number and size were quantified in each hemisphere, and the interhemispheric ratios (trained/untrained hemispheres) were used to compare the amounts of PKMζ in each group with those in controls (naive rats) (Figures 4 and S5 and Transparent Methods).…”
Section: Resultssupporting
confidence: 65%
“…Similar to LTP (Kelly et al, 2007), PKMζ protein increases in long-term memory without changes in mRNA levels. Therefore, we speculate that spatial conditioning causes PKMζ increases through new synthesis from pre-existing dendritic PKMζ mRNA (Muslimov et al, 2004) located at or near the specific synapses that are strongly activated during conditioning (Hernandez, Oxberry, Crary, Mirra, & Sacktor, 2014; Hernandez et al, 2003). The persistent local increases in the autonomously active kinase then maintain increased postsynaptic AMPAR-mediated synaptic transmission at these specific synapses by, for example, increasing the trafficking of GluA2 to postsynaptic sites through the action of N-ethylmaleimide sensitive factor (NSF) (Yao et al, 2008; Migues et al, 2010), so as to persistently modify the networks of neurons activated during learning to facilitate memory storage (Sacktor, 2011).…”
Section: Discussionmentioning
confidence: 99%